The Development of Android-Based Mobile Learning for Indonesian History Course at Vocational High School - Susila, Heni Rita; Isa, Yamanto; Wahidah, Nina Ikhwati (Universitas Negeri Malang, 2023)
This study aimed to develop android-based mobile learning for Indonesian History course at SMK YIS Martapura. This is a Research and Development (R&D) using the Alessi & Trollip model. Data collection techniques used questionnaire while research data were analyzed using the percentage formula. From the validation results, media experts scored got 88.69 percent belong to